On the topology of problems and their solutions - Agama, Theophilus (My University, 2023)
In this paper, we study the topology ofproblems and their solution spaces developed introduced in our first paper \cite{agama2022theory}. We introduce and study the notion of separability and quotient problem and solution spaces. This notions will form a basic underpinning for further studies on this topic.
Keywords: separable; quotient space; symmetric